A biopsychological review of gambling disorder - Quintero GC (Dove Medical Press, 2016)
Gabriel C Quintero Florida State University – Republic of Panama, Panama City, Panama Abstract: The present review is an overview of previous experimental work on biopsychological aspects of gambling disorder. It includes the topics 1) gambling disorder from the neuroimaging and electroencephalography (EEG) perspective, 2) cognitive, executive functioning, and neuropsychological aspects of gambling disorder, and 3) rodent models of gambling disorder. Penalties and losses in gambling can differ in terms of brain activity. Also, specific patterns of brain activity, brain anatomical traits, EEG responses, and cognitive and executive performance can discriminate pathological gamblers from nonpathological gamblers. Also, pathological gamblers can display dysfunction in such brain areas as the insula, frontal lobe, and orbitofrontal cortex. Pathological gambling is a heterogeneous disorder that can vary depending on the severity of cognition, the style of gambling (strategic or not), the prospect of recovery, proneness to relapse, and proneness to treatment withdrawal. Finally, based on rodent models of gambling, the appropriateness of gambling decision is influenced by the presence of cues, the activity of dopamine receptors, and the activity of some brain areas (infralimbic, prelimbic, or rostral agranular insular cortex). Pathological gamblers differed in terms of frontoparietal brain activation compared to nonpathological gamblers (if winning or losing a game). Pathological gamblers had dysfunctional EEG activity. The severity of gambling was linked to the magnification and content of cognitive distortions. The insula was fundamental in the distortion of cognitions linked to result analysis during gambling activity. Keywords: pathological gambling, biopsychology, human, rodent